A family of formulae for pi (2012)
A simple circle method for constructing rational points and tangents with straightedge and compass is introduced; taking the limit, this leads to a family of N formulae for π. The whole process is based on the derivation of a Pythagorean triple and the construction of the circle by irregular inscribed polygons with rational area. © 2012 Pushpa Publishing House.